PENINGKATAN HASIL BELAJAR DALAM PEMBELAJARAN IPA MENGGUNAKAN METODE EKSPERIMEN DI SDN 22 PONTIANAK BARAT - Juliani, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to improve the learning outcomes of students in science learning using the experimental method in class V SD. The research method used descriptive form of classroom action research (PTK). The procedure consisted of four stages including planning, implementation, observation, and reflection. Observation techniques of data collection instruments and measurement techniques. Data collector observation sheets and test questions. Based on data analysis known use of the experimental method of science learning can improve student learning outcomes with an average first cycle of 3.04, 3.34 second cycle, and the cycle III 3.85. The use of the experimental method can improve the skills of students with an increased percentage of 58.33% in the first cycle, the second cycle of 77.38%, 83.93% and the third cycle. The use of the experimental method of science learning can increase the average learning outcomes of students with average achieved 70 first cycle, second cycle 79.28, 87.14 and third cycle. It was concluded that the application of the experimental method of science learning in the process of forming the ground material can improve learning outcomes of students in class V SDN 22 Pontianak West. Keywords: Experimental Methods, Results Learning, Learning science